COLD REGIONS SCIENCE AND ENGINEERING MONOGRAPH 3, SECTION A2b: INVESTIGATION AND EXPLOITATION OF SNOWFIELD SITES - Mellor,Malcolm (1969)
The document covers the site investigations and laboratoty tests in connection with construction on a permanent snowfield, and then deals with the technology of excavation and building where snow is almost the only constructional material. The author draws heavily on the work of the Cold Regions Research and Engineering Laboratory (CRREL) in the development of Camp Century and other projects on the Greenland ice sheet and shows the application of the techniques to Antarctic Research Stations. (Author)